Manufacturing an active X‐ray mirror prototype in thin glass. (1st January 2016) - Spiga, D.; Barbera, M.; Collura, A.; Basso, S.; Candia, R.; Civitani, M.; Di Bella, M. S.; Di Cicca, G.; Lo Cicero, U.; Lullo, G.; Pelliciari, C.; Riva, M.; et al.
Abstract : Adjustable mirrors equipped with piezo actuators are commonly used at synchrotron and free‐electron laser (FEL) beamlines, in order to optimize their focusing properties and sometimes to shape the intensity distribution of the focal spot with the desired profile. Unlike them, X‐ray mirrors for astronomy are much thinner in order to enable nesting and reduce the areal mass, and the application of piezo actuators acting normally to the surface appears much more difficult. There remains the possibility to correct the deformations using thin patches that exert a tangential strain on the rear side of the mirror: some research groups are already at work on this approach. The technique reported here relies on actively integrating thin glass foils with commercial piezoceramic patches, fed by voltages driven by the feedback provided by X‐rays, while the tension signals are carried by electrodes on the back of the mirror, obtained by photolithography. Finally, the shape detection and the consequent voltage signal to be provided to the piezoelectric array will be determined by X‐ray illumination in an intra‐focal setup at the XACT facility. In this work, the manufacturing steps for obtaining a first active mirror prototype are described.